2020
DOI: 10.1186/s43008-020-00042-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fungal communities associated with different organs of the mangrove Sonneratia alba in the Malay Peninsula

Abstract: Mangrove forests are key tropical marine ecosystems that are rich in fungi, but our understanding of fungal communities associated with mangrove trees and their various organs remains limited because much of the diversity lies within the microbiome. In this study, we investigated the fungal communities associated with the mangrove tree Sonneratia alba throughout Peninsular Malaysia and Singapore. At each sampling location, we collected leaves, fruits, pneumatophores and sediment samples and performed amplicon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
3
9
0
Order By: Relevance
“…We show that microbial communities are significantly different between locations despite the short distances separating them, and communities can be further differentiated dependent upon the structure sampled (e.g., leaf, vesicle or holdfast), with holdfasts appearing to have the most distinct community composition. These findings are in agreement with other work from the region that shows microbial community divergence at small spatial scales in a diverse range of marine taxa such as seagrasses [33], mangroves [32] and corals [60].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We show that microbial communities are significantly different between locations despite the short distances separating them, and communities can be further differentiated dependent upon the structure sampled (e.g., leaf, vesicle or holdfast), with holdfasts appearing to have the most distinct community composition. These findings are in agreement with other work from the region that shows microbial community divergence at small spatial scales in a diverse range of marine taxa such as seagrasses [33], mangroves [32] and corals [60].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis shows a differentiation in the microbial communities associated with the structures sampled, with the holdfast harboring the most distinct community. This is in line with studies performed on other marine organisms from the region, which have shown microbial community divergence over small spatial scales in seagrasses, mangroves and corals [32][33][34]; the same S. ilicifolium structures have also been shown to harbor distinct fungal communities in Singapore [39]. Like other studies examining algal associated microbiota, we show that holdfasts and leaves contain a large proportion of Alphaproteobacteria and Gammaproteobacteria; however, noticeable by their absence in both of these structures, samples collected in Singapore do not contain the class Flavobacteria in comparison to those collected from temperate environments [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, microbial communities could become homogenised between plant members of the same species, especially when taking into account the high dispersal potential microbes have, or, "everything is everywhere: but the environment selects" (O'Malley, 2008), or in this case the plant selects. Yet, research is frequently showing discrete microbial (fungi and bacteria) communities do exist in different sampling locations within the same species (e.g., seagrasses and mangorves) (Ettinger et al, 2017;Fahimipour et al, 2017;Crump et al, 2018;Wainwright et al, 2019a;Lee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental variation will inherently be small at this local scale compared to that across broader spatial scales where community‐genetic effects may be less influential (Hughes and Stachowicz, 2009; Tack et al, 2010; Gossner et al, 2015; but see Bangert et al, 2006a; Davies et al, 2014; Lamit et al, 2015). Spatial effects on foliar endophytic fungal communities in mangroves are evident across greater geographic distances (Lee et al, 2019, 2020). As such, the relationship between mangrove host‐tree genetic variation and associated fungal communities documented here may vary depending on the spatial extent under consideration and warrants additional research.…”
Section: Discussionmentioning
confidence: 99%